Dampak Pengalaman Traumatis Terhadap Perkembangan Psikologis Remaja - Yunita Nadzilatun Nisa (Universitas Sanata Dharma, 2026)
Trauma experienced during childhood can impact adolescence and hinder psychological development. Adolescents who have experienced traumatic experiences often find it difficult to control their emotions, build relationships with others, and maintain a positive self-image. This article examines the impact of traumatic experiences on adolescent development. The author used a literature review method by gathering information from relevant journals and books on trauma and adolescent psychological development. The results indicate that traumatic experiences can cause various psychological problems such as emotional disturbances, inappropriate behavior, and difficulties with social interactions. Therefore, understanding the impact of trauma on adolescents is crucial to provide a basis for prevention and psychological support. This article is expected to provide theoretical insight and serve as a reference for further research on adolescent mental health.